2018
DOI: 10.1016/j.dib.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

datasets on employee value proposition (evp) and performance of selected fast moving consumer goods (FMCGs) firms in Nigeria

Abstract: The article presented an integrated dataset on employee value proposition (EVP) and performance of selected Fast Moving Consumer Goods (FMCGs) firms in Nigeria. The study adopted quantitative approach with a descriptive research design to establish the major determinants of employee value proposition. The population of this study included staff and management of the selected firms. Data was analysed with the use of measurement and structural equation modelling and the field data set is made widely accessible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This implies that a unit change of academic staff retention will lead to increase in sustainable performance of universities by 19%. The current study finding was similar to previous findings 4 , 8 , 13 , 21 , 34 , 35 , 41 , 45 , 47 . These researchers predicted that rewards and recognition, as well as employee intention to stay in the organization, are positively correlated, meaning that if an organization provides appropriate rewards and recognition to its employees for doing good, the retention rate will improve.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This implies that a unit change of academic staff retention will lead to increase in sustainable performance of universities by 19%. The current study finding was similar to previous findings 4 , 8 , 13 , 21 , 34 , 35 , 41 , 45 , 47 . These researchers predicted that rewards and recognition, as well as employee intention to stay in the organization, are positively correlated, meaning that if an organization provides appropriate rewards and recognition to its employees for doing good, the retention rate will improve.…”
Section: Discussionsupporting
confidence: 93%
“…Students are overcrowded in rooms with some hanging on to windows where ventilation is poor 32 , or flock around shades in the open. Electricity, enabling comfort, skills acquisition or laboratory work, is often absent, public address systems inadequate and digital technology to assist with knowledge transfer and interactive sessions - internet access, smart boards - absent in many institutions 31 , 33 , 34 .…”
Section: Introductionmentioning
confidence: 99%
“…On one side you have the employer providing remuneration, employee benefits, performance and recognition incentives, talent development opportunities, work-life initiatives and a healthy organisational culture (South Africa 2019); on the other side you have the employee whose engagement with the EVP determines their level of effort in bringing the vision of the institution to life. The purpose of the EVP is to attract, engage and subsequently retain employees to achieve institutional success (Salau et al 2018). It is of critical importance that employers should focus on a competitive EVP and a package offering to maintain a competitive edge.…”
Section: Literature Review the Function Of The Employee Value Proposi...mentioning
confidence: 99%
“…It is of critical importance that employers should focus on a competitive EVP and a package offering to maintain a competitive edge. Salau et al (2018) describe the EVP as the value or benefit an employee derives from their membership of an organisation. It has been suggested that the EVP is a determinant of employee engagement and retention, with a direct effect on critical business outcomes.…”
Section: Literature Review the Function Of The Employee Value Proposi...mentioning
confidence: 99%
“…From the previous study, career growth and reward can be considered as predictive determinants of EVP for increasing performance (Salau et al, 2018). Based on the overview from questionnaires, its explains which factors are most significant to increase performance of employee.…”
Section: Analysis Understanding Employee Value Propositionmentioning
confidence: 99%